Effects of Kabat rehabilitation versus mime therapy on facial disability and synkinesis in patients of Bell’s palsy - Amjad, Ayesha; Ayesha Jamil; Nida Fatima; Hira Bano Javaid; Hafsa Zahid (Journal of the Pakistan Medical Association, 2024)
Objective: To compare the effects of Kabat rehabilitation and Mime therapy on facial disability and synkinesis in patients with Bell’s palsy. Method: The single-blind, randomised clinical trial was conducted at the Physiotherapy Department of the University of Lahore Teaching Hospital, Lahore, Pakistan, from May to October 2023, and comprised adults of either gender aged 25-50 years having sub-acute or chronic unilateral Bell’s palsy of non-congenital origin. The patients were randomised into Kabat rehabilitation group A and mime therapy group B. Conventional physical therapy was given to both groups additionally. Facial disability was assessed using the Facial Disability Index scale, and synkinesis was observed using the House-Brackmann Facial Nerve Grading Scale. Data was analysed using SPSS 25. Results: Of the 72 patients, 41(56.9%) were females and 31(43.1%) were males. The overall mean age was 37.77±6.98 years, mean body mass index was 25.71±5.71kg/m2 and 41(56.9%) patients had left-sided palsy. Facial disability and synkinesis were significantly different in both groups post-intervention (p<0.001), while intergroup differences were significant in the 3rd and 6th weeks (p<0.001). Conclusion: Kabat rehabilitation led to more significant improvements in synkinesis and facial disability compared to mime therapy. Clinical Trial Number: Clinical trials.gov registration id: NCT06029855. Key Words: Bell’s palsy, Disability, Rehabilitation, Synkinesis.